PENGEMBANGAN MEDIA E-COMIC INTERAKTIF UNTUK MATA PELAJARAN MATEMATIKA DI KELAS IV MI MAHIR AR-RIYADL SURABAYA - Pawestri, Dwi Almy; Amin, Siti Maghfirotun; Hartatik, Sri; Rulyansah, Afib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics is one of the main subjects that must be taught at school. Good mathematical skills are needed to overcome various daily challenges. However, many students still have difficulty understanding mathematical concepts especially when faced with story problems and student participation in learning is also still low. The purpose of this research is to determine the validity, practicality, and effectiveness of interactive e-comic learning media. The research method used is Research and Development (R&D) with a 4D development model (Define, Design, Develop, and Disseminate) which is modified into 3D. The instruments used are validation sheets, student and teacher response questionnaires, and tests. The validity of the product is obtained from the media expert validation results of 94%, categorized as very valid. The practicality of the e-comic is obtained from student responses with a percentage of 93% and teacher responses at 96%, both categorized as very practical. The effectiveness of the product is determined from students' learning outcomes tests. Based on the student learning achievement test, the percentage of classical completeness is 100% with the category of students meeting the criteria for achieving learning objectives, and interactive e-comic s are effective to use. Based on the results of this study, interactive e-comic s can be said to be valid, practical, and effective for use in 4th grade Mathematics subjects.